2020
DOI: 10.1111/ppa.13158
|View full text |Cite
|
Sign up to set email alerts
|

Variation in aggressiveness of Hymenoscyphus fraxineus genotypes amid the ash dieback epidemic

Abstract: The ascomycete Hymenoscyphus fraxineus causes devastating damage to the European common ash (Fraxinus excelsior). The fungus originates from Asia, where it coexists with native ash species and completes its life cycle by sporulating on degrading ash leaf litter on the forest floor. Given this life cycle of the fungus, genotypes of H. fraxineus with varying degrees of aggressiveness may coexist in infected European ash forests. To test this hypothesis, we cultured 19 single‐spore isolates from apothecia collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(47 reference statements)
2
7
2
Order By: Relevance
“…In line with other studies, we found significant differences between isolates in lesion length (Kosawang et al, 2020;Kowalski & Holdenrieder, 2009;Lygis et al, 2017) and also in the percentage of inoculations resulting in lesions (Adamčíková et al, 2018). We found that the isolates CBS 145275 and CBS 122504 always induced lesions in both experiments.…”
Section: Percentage Of Inoculations Inducing Lesions and Isolate Viru...supporting
confidence: 92%
“…In line with other studies, we found significant differences between isolates in lesion length (Kosawang et al, 2020;Kowalski & Holdenrieder, 2009;Lygis et al, 2017) and also in the percentage of inoculations resulting in lesions (Adamčíková et al, 2018). We found that the isolates CBS 145275 and CBS 122504 always induced lesions in both experiments.…”
Section: Percentage Of Inoculations Inducing Lesions and Isolate Viru...supporting
confidence: 92%
“…Surpassing the tolerance offered by a single SNP would not make a large quantitative difference to the overall tree phenotype. Combined with recent results which present evidence that the biology of the pathogen does not favour selection of high virulence (Kosawang et al, 2020), and evidence of superior reproductive success of less susceptible individuals, gives some hope for the future of common ash (Semizer-Cuming et al, 2019. High mortality among the current generation is an acute concern but higher fitness of tolerant individuals, combined with restoration efforts and breeding programs will strongly support the continuation of F. excelsior in European forests.…”
Section: High Phenotypic Variance Is Explained By a Relatively Low Nu...mentioning
confidence: 90%
“…Parafilm was wrapped around the stem. A culture of H. fraxineus strain 18.3 (Kosawang et al ., 2020) was used as a positive control and sterile wood plugs as negative controls. Three biological replicates were performed for each inoculation type (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We address this question by studying three Hymenoscyphus species closely related to H. fraxineus : H. albidus , isolated from European ash growing in Wales (UK), H. koreanus , and H. occultus ; two newly-discovered species of Asian origin and not (yet) introduced to Europe; they have been isolated by Gross and Han (2015) from petioles of Korean ash ( F. chinensis subsp. rhynchophylla ) (Gross and Han, 2015; Kosawang et al ., 2020).…”
Section: Mainmentioning
confidence: 99%